2020
DOI: 10.3390/microorganisms8040528
|View full text |Cite
|
Sign up to set email alerts
|

Gene Expression Profile of Mexican Lime (Citrus aurantifolia) Trees in Response to Huanglongbing Disease caused by Candidatus Liberibacter asiaticus

Abstract: Nowadays, Huanglongbing (HLB) disease, associated with Candidatus Liberibacter asiaticus (CLas), seriously affects citriculture worldwide, and no cure is currently available. Transcriptomic analysis of host-pathogen interaction is the first step to understand the molecular landscape of a disease. Previous works have reported the transcriptome profiling in response to HLB in different susceptible citrus species; however, similar studies in tolerant citrus species, including Mexican lime, are limited. In this wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 50 publications
2
20
0
Order By: Relevance
“…A study on the Arabidopsis oomycete downy mildew pathogen found that marked differences were observed between early and late stages of infection, but a gene encoding a LRR-RLK was constantly upregulated, and a knockout mutant showed reduced pathogen infection (Hok et al, 2011 ). Similarly, comparing the present study with several previous transcriptomic studies on Ca Las-infected citrus plants (Albrecht and Bowman, 2008 ; Liao and Burns, 2012 ; Martinelli et al, 2012 ; Aritua et al, 2013 ; Xu et al, 2015 ; Wang et al, 2016 ; Arce-Leal et al, 2020 ), significant differences were observed between early and late stages of infection. It is speculated that this RLK (ciclev10014641m) plays a crucial role in Ca Las and citrus interaction.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…A study on the Arabidopsis oomycete downy mildew pathogen found that marked differences were observed between early and late stages of infection, but a gene encoding a LRR-RLK was constantly upregulated, and a knockout mutant showed reduced pathogen infection (Hok et al, 2011 ). Similarly, comparing the present study with several previous transcriptomic studies on Ca Las-infected citrus plants (Albrecht and Bowman, 2008 ; Liao and Burns, 2012 ; Martinelli et al, 2012 ; Aritua et al, 2013 ; Xu et al, 2015 ; Wang et al, 2016 ; Arce-Leal et al, 2020 ), significant differences were observed between early and late stages of infection. It is speculated that this RLK (ciclev10014641m) plays a crucial role in Ca Las and citrus interaction.…”
Section: Discussionsupporting
confidence: 83%
“…Several studies have demonstrated the complexity of pathogen, vector, and host interactions, and revealed that Ca Las infection primarily affects source-sink relationships, signaling pathways, and nutrient distribution, thereby creating environments favorable for colonization and proliferation within citrus plants (Martinelli et al, 2012 ; Zhao et al, 2013 ; National Academies of Sciences, 2018 ). Transcriptomic profiling of citrus– Ca Las interactions have been performed through microarray and high-throughput sequencing technologies, with different citrus tissues and pretreatments from both sensitive and tolerant citrus species (Albrecht and Bowman, 2008 ; Fan et al, 2012 ; Liao and Burns, 2012 ; Martinelli et al, 2012 ; Aritua et al, 2013 ; Xu et al, 2015 ; Yu Q. et al, 2017 ; Arce-Leal et al, 2020 ). Interestingly, on the one hand, even in the sensitive varieties, studies revealed that large numbers of defense-related genes are induced after Ca Las infection, which means that the citrus plants have the ability to launch the defense response, despite mostly losing the battle (Kim et al, 2009 ; Fan et al, 2012 ; Koh et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, gene expression profile of tolerant Mexican lime and susceptible Washington navel orange in response to Ca. L. asiaticus infection uncovered that the expression of multiple genes related to starch synthesis was significantly induced at the symptomatic stage, while no difference at the asymptomatic stage compared to healthy counterparts was observed (Arce-Leal et al, 2020;Chin et al, 2020). The consistent results from this study at the protein level confirmed the increased abundance of starch synthesis-related proteins such as glgC, GBSS1, and GBE in the petiole of leaves with typical symptoms.…”
Section: Deregulation Of Starch Biosynthesis As a Hallmark Of Hlb Symptom Establishmentsupporting
confidence: 81%
“…The identification of candidate genes is a prerequisite for the application of new genome editing techniques by which targeted genetic modifications can lead to the introduction of precise changes directly into the genome of commercial varieties, offering an alternative to traditional methods of genetic improvement [ 19 , 20 , 21 ]. Different authors in the last years conducted transcriptomic analysis to better understand Citrus plants response to biotic stress caused by pathogens [ 22 , 23 , 24 , 25 , 26 , 27 ]. Specifically, a study evaluated the transcriptional reprogramming of both rough lemon and sweet orange leaf tissue during the asymptomatic stage of infection caused by Candidatus Liberibacter asiaticus.…”
Section: Introductionmentioning
confidence: 99%